Peningkatan Hasil Belajar Operasional Spreadsheet Jenis dan Fungsi dengan Rumus Statistik Akuntansi melalui Demonstrasi dan Presentasi - NURBAITI SALPIDA GINAYANTI (Fakultas Ekonomi Universitas Negeri Jakarta, 2016)
ABSTRACT The research was purposed to find out the effectiveness of demonstration and presentation models are able to improve study result of students in operating Spreadsheet type and function by statistics in X Accounting 1 in SMKN 48 at Academic Year 2014/2015. The reasearch was conducted on August-November 2014. The method of the research was Action Research (PTK) which was conducted in two cycles. Demonstration and Presentation were used as learning cycle model. A cycle consisted in three times of meetings and in the third meeting was done Post test. The indicators have been achieved by the result of research. As the expectation, in the second cycle, namely the number of students got the highest points was 97,45% and average value was 80,79%. In conclusion, demonstration and presentation are able to improve students’ study result in operating spreadsheet type and function by statistics if it was implemented appropriately in X Accounting 1 in SMKN 48 Jakarta.Keywords : Demonstration, Presentation, Spreadsheet